Estabilidad laboral de los trabajadores calificados como sustitutos, garantizando los derechos de las personas con discapacidad. - Quezada Ramírez, Miriam Herlitta (2024)
The main objective of this research work was to carry out a conceptual, doctrinal and legal study about the reinforced job stability of workers qualified as substitutes, in order to guarantee the rights of people with disabilities. The investigation addressed in a legal, dogmatic, jurisprudential manner, unjustified dismissal, substitute, disability as a component of the right to work Despite the recognition of the right to work of people with disabilities through substitutes, at a supranational and constitutional level, with research work, it was determined through surveys, jurisprudence, doctrine and comparative regulations that have been imposed in our country. a limit to the guarantee of reinforced job stability for people with disabilities through the standard for the qualification and certification of substitutes issued by Ministerial Agreement MDT-2018-180, for reaching the age of majority and not meeting the established percentage of severe disability to be able to continue with the legitimate expectation of working. Scientific, analytical, synthetic, exegetical methods were used; and, hermeneutic. Obtaining as one of the most relevant results, that the norm under study restricts labor rights of people with disabilities, the principle of normative hierarchy is affected; and, of non-restriction, preventing the equal application of labor principles, to people with disabilities who have a substitute.